Star shaped gold nanoparticles for surface enhanced Raman spectroscopy - Emil Fazira Kamari (2013)
Gold nanoparticles play an integral part in the world of nanomaterials and nanotechnology. Nowadays, there has been increased attention given to nanostars specifically, as it was discovered that the tips of these nanostars provide hotspots and better enhancement of Plasmon resonance. This paper aims to successfully synthesise gold nanostars of varying sizes and dimensions, as well as investigate their surface-enhanced Raman spectroscopy (SERS) properties. Self-assembly of these gold nanoparticles into a monolayer is also explored, and the challenges faced analysed. While the synthesis of gold nanostars is accomplished and analysed in detail using UV-Vis spectroscopy, visual images and TEM images, the gold nanostars’ SERS properties are analysed using SERS spectrum. The use of Malachite Green (MG) as Raman dye is also included in the experiment. There is room for improvement in terms of materials used in the synthesis of gold nanostars to ensure maximum adsorption of molecules. Included are suggestions for better methods for analysis as well.